Development of Science e-Book Containing Gamelan's Local Wisdom Based on STEAM-POE to Facilitate Students' Love of Local Culture - Dwi Agnes Setianingrum; Dhiarrafii Bintang Matahari; Jumadi Jumadi; Insih Wilujeng (Jurnal Penelitian Pendidikan IPA, 2023)
Science learning is still not integrated with the surrounding environment so that students tend not to be able to recognize the local wisdom of their area. Even though science learning contains local wisdom, it can increase students' love of local culture, creating contextual and meaningful learning. To overcome this, research was carried out through the development of a science e-book containing gamelan's local wisdom based on STEAM-POE. This development research aims to (1) determine the validity of a science e-book containing gamelan's local wisdom based on STEAM-POE (2) find out student’s love local culture. This study uses the Thiagarajan 4D development model (Four-D Model), which consists of four stages, namely the definition stage, the design stage, and the development stage. The dissemination stage was not carried out, this research was only limited to product feasibility testing. The research design used was the one-group posttest-only design. The sample in this study was class VIII E, totaling 32 people. The collection techniques used were questionnaires and documentation. The results of the material expert validity test showed that the science e-book containing gamelan's local wisdom based on STEAM-POE was declared very valid with an Aiken's V value of 0.992 and the validity of the teaching material expert showed that the science e-book containing gamelan's local wisdom based on STEAM-POE was declared very valid with Aiken's V score of 1.0. Students' love of local culture after using the science e-book containing local gamelan's local wisdom based on STEAM-POE shows a score of 3.266 in the very good category. Students' love of local culture also gets a variable score of 52.5 which is included in the high category.